The Relationship Between the Formation of Study Groups and Student Learning Independence - Zahra, Alvina (Medan State University, 2023)
The purpose of this study was to determine the “Relationship Between The Formation Of Study Groups And Student Learning Independence. This research uses a quantitative approach with the correlation method. In this study, the sample was 70 students in class XI IPS SMA Negeri 8 Medan. The data collection technique used in this research was a questionnaire using a Likert scale. The validity of the instrument is obtained using the product moment correlation formula, while the reliability of the instrument is obtained using the Cronbach's Alpha formula. Data were analyzed using Product Moment Correlation Statistics to test the hypotheses in the research with the help of SPSS 29 for Windows. The analysis results show r = 0.541 and Rsquare = 0.321 and a significant value of 0.001 (p<0.05). Based on the results of this research, the research hypothesis